INVESTIGATING STUDENTS' SCIENTIFIC LITERACY AND CREATIVITY THROUGH STEM-ENGINEERING DESIGN PROCESS IN ELEMENT, COMPOUND, AND MIXTURE TOPIC - Andini Fajarwati, - (2023)
STEM-Engineering Design Process is one of the learning model that emphasize students to do the engineering activity to solve the real life problem. This study aims to investigate the effect of STEM-Engineering Design Process on students' scientific literacy and creativity in element compound, and mixture topic. Quasi-Experimental design is use in this study. The implementation of STEM-engineering design process was conduct in experiment class, while control class carried out conventional learning. Both classes are making water filtration tool. Purposive technique sampling was carried out to choose the sample with the certain category of 9th grade students in one of the private school in Bandung, West Java, Indonesia. Students ranges in age 14-15 years old and were divide in experiment and control class. Each class has 19 students. This research use scientific literacy objective test and creativity questionnaire Likert scale to collect the data. The result of this study showed there is significant difference in students' scientific literacy and no significant difference in students' creativity between experiment and control class. The N-Gain score for scientific literacy of experiment and control class is 0.38 and 0.11 which describe as medium and low improvement. While for creativity, N-Gain score in experiment and control class is 0.06 and 0.03 which describe as low. From this, researcher conclude that STEM-engineering design process has positive impact on students' scientific literacy and creativity in learning element compound, and mixture.